2014
DOI: 10.1530/eje-14-0256
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in glucocorticoid metabolism are associated with later development of adverse metabolic phenotype

Abstract: Objective: Dysregulation of enzymes that control local tissue steroid metabolism has been implicated in the pathogenesis of obesity and insulin resistance; however, longitudinal changes in glucocorticoid metabolism have not been investigated. This study was performed to evaluate the role of glucocorticoid metabolism in the development of insulin resistance and obesity and to identify biomarkers for future development of metabolic disease. Design: This was a prospective longitudinal observation study conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Alternatively, obesity itself might be the primary stimulus for either global overactivation of the HPA axis resulting in increased circulating cortisol concentrations, or increases in cortisol availability or activity at the level of the target tissues, or both. Chronically increased glucocorticoid production and increased hair cortisol (consistent with chronic free cortisol excess) have been associated with obesity in several studies in people,38, 39, 40, 41 and are consistent with long‐standing over‐activity of the HPA axis in obese states. Tissue cortisol metabolism also appears to be altered in obesity.…”
Section: Discussionmentioning
confidence: 60%
“…Alternatively, obesity itself might be the primary stimulus for either global overactivation of the HPA axis resulting in increased circulating cortisol concentrations, or increases in cortisol availability or activity at the level of the target tissues, or both. Chronically increased glucocorticoid production and increased hair cortisol (consistent with chronic free cortisol excess) have been associated with obesity in several studies in people,38, 39, 40, 41 and are consistent with long‐standing over‐activity of the HPA axis in obese states. Tissue cortisol metabolism also appears to be altered in obesity.…”
Section: Discussionmentioning
confidence: 60%
“…One of the likely explanations for this observation could be a potential misclassification of patients; for example, one study described that a significant proportion of patients with NF adrenal tumors developed adrenal insufficiency after surgery, clearly suggesting that autonomous glucocorticoid production was not recognized preoperatively (47). Overall glucocorticoid production has been linked to HTN, abnormal glucose tolerance and increased BMI (50). Thus, it is also possible that a temporary reduction of the overall glucocorticoid load caused by unilateral adrenalectomy could have contributed to a short-term BP improvement described in patients with NF adrenal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Activity increases with BMI and decreases with weight loss and in addition predicts the future development of an adverse metabolic phenotype (123)(124)(125). Specifically in the context of NAFLD, 5αR activity is generally reported as increased (113) and isotope clearance studies using liquid chromatography tandem mass spectrometry have demonstrated increased cortisol clearance (126) .Differences in activity according to stage of disease have also been proposed with increased 5αR activity in patients with NASH and not simple steatosis.…”
Section: α-Reductasementioning
confidence: 99%